STRATEGI KONSERVASI PELESTARIAN DAN NILAI KEPENTINGAN BUDAYA (INDEX OF CULTURAL SIGNIFICANCE) PISANG ROID LOKAL JATIGEDE: STRATEGI KONSERVASI PELESTARIAN DAN NILAI KEPENTINGAN BUDAYA (INDEX OF CULTURAL SIGNIFICANCE) PISANG ROID LOKAL JATIGEDE - Ismail, Ade; Karuniawan, Agung; Qosim, Warid Ali; Maharani, Yani; Pratiwi, Vika Faraditha; Wijaya Kusumah, Fajar Maulana (Jurnal Kajian Budaya dan Humaniora, 2023)
Banana is one of the community's most cultivated and utilized agricultural commodities. Currently, Indonesia only has 101 registered types of local varieties of bananas, one of which is Roid bananas from the Jatigede District. The local community has not taken care of Roid bananas and let them grow wildly. The exploitation of Roid usage without any conservation and preservation efforts can affect the scarcity of banana Roid as a genetic resource. Therefore, it is necessary to identify the istribution and genetic diversity of banana Roid through in situ exploration and characterization. This study aimed to identify genetic diversity's potential and arrange the conservation strategy for banana Roid (Musa spp.) in Jatigede District. This activities was conducted in April – November 2022 in Ciranggem Village, Jemah Village, and Mekarasih Village. The data was collected by exploration, survey, and interview methods. Banana Rod has the highest ICS value of 99 compared to other types of bananas. The proposed method of conservation and preservation of local varieties is in situ conservation centered in Mekarasih Village, Jatigede District, Sumedang